The Quality of School Bus Services for Students in the City of Alor Setar and the Town of Jitra, Kedah Darul Aman - Siti Aimuni, Abu Hassan; Mazdi , Marzuki (GEOGRAFI, 2024)
This study aims to identify the quality of school bus services in the city of Alor Setar and the city of Jitra, Kedah based on six criteria: safety, availability/time, cost, comfort, physical condition, and convenience. The study employed a quantitative approach and a questionnaire survey design. The respondents consisted of 62 students of SMK Tengku Laksamana, Alor Setar, and 34 students of SMK Tanjung Pauh, Jitra, who used the school bus service. We conducted descriptive analysis (frequency, percentage, mean, and standard deviation) and inferential analysis (Chi-Square test) to identify differences in service quality between the two schools. A study showed that SMK Tengku Laksamana has better service quality than SMK Tanjung Pauh in all six areas: safety (4.20), availability/time (4.27), cost (4.25), comfort (4.14), physical (4.46), and convenience (3.77). The safety score was 3.27, availability/time (2.92), cost (3.19), comfort (2.99), physical (3.55), and convenience (3.31). The Chi-Square Test found that there was no significant difference for safety criteria between the two schools (p > 0.05). However, other criteria such as time availability, cost, comfort, physicality, and convenience show significant differences (p < 0.05), which indicates that there is a difference in the quality of school bus services in Alor Setar and Jitra. In conclusion, the quality of school bus service at SMK Tengku Laksamana is better than at SMK Tanjung Pauh. This study recommends enhancing the school bus service at SMK Tanjung Pauh, particularly in areas such as physical condition, convenience, cost, and comfort. Authorities and school bus service managers need to consider this finding in order to improve service quality and increase user satisfaction.